MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK MELALUI MODEL KOOPERATIF THINK PAIR SHARE - Ummi Kalsum (Integral : Pendidikan Matematika, 2020)
ABSTRACT The purpose of this study is to determine whether the application of Think Pair Share learning models can improve mathematics learning outcomes. This research uses the Classroom Action Research (CAR) method which is carried out in two cycles in which each cycle is passed through four stages, namely: (1) action planning, (2) action implementation, (3) action observation, and (4) reflection of action. The results of this study indicate that the application of Think Pair Share (TPS) learning models can improve mathematics learning outcomes. This is supported by the following facts: (1) The activeness of students in the teaching and learning process increased by 6.3%. These results are shown in cycle 1 of 76.55% and in cycle 2 of 82.85%. (2) The average value of the test results obtained by students increased by 0.92%. These results are shown in cycle 1 of 83.31% and in cycle 2 of 84.23%; (3) Completeness of learning outcomes increases by 5%. These results are shown in cycle 1 of 77.5% and in cycle 2 of 82.5%. (4) The activeness of students in discussions has the greatest increase compared to the results of tests and the completeness of the learning outcomes of other students. This is due to students giving a positive response to the tasks given by the teacher by actively discussing in pairs / groups. Keywords :Classroom Action Research, Think Pair Share, Learning Outcomes. ABSTRAK Tujuan Penelitian ini adalah untuk mengetahui apakah penerapan model pembelajaran Think Pair Share dapat meningkatkan hasil belajar matematika. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan sebanyak dua siklus di mana masing-masing siklus dilalui dengan empat tahapan, yaitu: (1) perencanaan tindakan, (2) pelaksanaan tindakan, (3) observasi tindakan, dan (4) refleksi tindakan. Hasil penelitian ini menunjukkan bahwa penerapan model pembelajaran Think Pair Share ( TPS ) dapat meningkatkan hasil belajar matematika. Hal tersebut didukung oleh fakta-fakta sebagai berikut: (1) Keaktifan siswa dalam proses belajar mengajar meningkat sebanyak 6,3 %. Hasil tersebut ditunjukkan pada siklus 1 sebesar 76,55 % dan pada siklus 2 sebesar 82,85%. (2) Nilai rata-rata hasil tes yang diperoleh siswa meningkat 0,92 %. Hasil tersebut ditunjukkan pada siklus 1 sebesar 83,31% dan pada siklus 2 sebesar 84,23%; (3) Ketuntasan hasil belajar meningkat sebesar 5%. Hasil tersebut ditunjukkan pada siklus 1 sebesar 77,5% dan pada siklus 2 sebesar 82,5%. (4) Keaktifan siswa dalam diskusi mengalami peningkatan terbesar dibandingkan dengan hasil tes dan ketuntasan hasil belajar siswa lainnya. Hal tersebut disebabkan siswa memberi respon yang positif terhadap tugas yang diberikan guru dengan aktif berdiskusi dalam pasangan/ kelompok. Kata-kataKunci:Penelitian Tindakan Kelas, Think Pair Share, Hasil Belajar.